2006
DOI: 10.1007/s10209-006-0054-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic approach to the development of research-based web design guidelines for older people

Abstract: This paper presents a systematic approach to the development of a set of research-based ageingcentred web design guidelines (SilverWeb Guidelines). The approach included an initial extensive literature review in the area of human-computer interaction and ageing, the development of an initial set of guidelines based on the reviewed literature, a card sorting exercise for their classification, an affinity diagramming exercise for the reduction and further finalisation of the guidelines, and finally a set of heur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 36 publications
3
79
0
1
Order By: Relevance
“…However, this is no longer the case, as is evident from the fact that they are now one of the fastest growing users of the Internet [1,9]. Recent studies show that older adults are now as enthusiastic as younger adults in using the web [38]. The Internet is known to decrease isolation Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is no longer the case, as is evident from the fact that they are now one of the fastest growing users of the Internet [1,9]. Recent studies show that older adults are now as enthusiastic as younger adults in using the web [38]. The Internet is known to decrease isolation Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Introductionmentioning
confidence: 99%
“…Web design guidelines to address the web experiences of older users can be found in [25,3], while a survey on touch-based mobile phone interface for the elderly can be found in [2]. In our implementation we used a tablet because it has been found that elderly users are very receptive to these devices [24].…”
Section: Multi-modal Interface For Elderly-robot Interactionmentioning
confidence: 99%
“…However, this increase worldwide in numbers of the aged means that the need for online and mobile technology services will only increase. By 2020, it is anticipated that there will be more than a billion older adults, making it essential that websites be designed for easy use by the elderly [1]. P Online banking is an exchange that employs laptops or other mobile devices, such as smart phones and tablets.…”
Section: Introductionmentioning
confidence: 99%